Reformulación del rol político de la diosa Venus en el De rerum natura de Tito Lucrecio Caro (siglo I a.C.) - Salas, Mayra (2019)
“Reformulation of the Political Role of the Goddess Venus in the De rerum natura by Titus Lucretius Carus (1st century BC)”. The invocation of the goddess Venus in the proem to the first book of De rerum natura is one of the most memorable in the history of literature, as well as one of the most unsettling texts in history that deny all divine influence in human affairs. This article seeks to find, in the presence of the goddess Venus throughout the poem, an ordering dimension that would distinguish it from any traditional divine entity. We propose, then, that our goddess personifies the ordering of nature and the reintegration of the social order into the natural order. The philosopher Lucretius, in his struggle against divinity, presents Venus as an element that expresses a rationalization of the universe in political terms. To support our hypothesis, we have accessed the Latin of Lucretius to identify in it concepts of Roman politics unquestionably associated with the government of nature, which our goddess presides over.